Adaptability of COVID-19 Safety Guidelines in Building Construction Sites in Anambra State, Nigeria - , F. O. Ezeokoli; , M. I. Okongwu; , D. O. Fadumo (Archives of Current Research International, 2020)
Aim: The study evaluates how COVID-19 safety rules were applied in construction sites in Anambra state, Nigeria. Study Design: The study being a survey research was effected through literature review, a well-structured questionnaire and interview. Place and Duration of the Study: The study was conducted in Anambra State, Nigeria for a period of 6 months. Methodology: Being a survey research, questionnaire containing information relating to COVID-19 guidelines were randomly administered to selected construction practitioners in Anambra State, Nigeria. Accordingly, a total of 84 questionnaires were administered while 81 copies were completed, returned and found useful. This corresponds to a response rate of 96%. The data were analyzed using Relative importance index and ranked appropriately. Results: The study found out that maintaining stay at home policy if one is sick (0.827), use of face covering/face mask (0.793), placing wash stations or hand sanitizers in multiple locations at construction sites (0.714), maintaining a daily attendance log for all staff and visitors (0.689) and use of provision of personal protective equipment (0.679) are the commonly used covid-19 safety guideline in the study area. The study also, observed that greater percent of the COVID-19 safety guidelines are rarely applied in the study area. Conclusion: The study concluded by recommending that construction sites in the study area should integrate the recommended safety guidelines in its daily operations and/or activities despite the fact that such practices may attract extra cost and disrupt site activities were contacts are necessary as well as take more time to adjust to the new normal in construction.